Some Notes on the Ideals and Goals of Indonesia’s National Education System and the Inconsistency of its Implementation: A Comparative Analysis - Soedijarto (Journal of Indonesian Social Sciences and Humanities, 2009)
The Republic of Indonesia’s State Constitution of 1945 adopted a basic policy that obliges the government to run one national education system. It would seem it was the belief of the Founding Fathers when they drafted the constitution that education would be the strategic vehicle for ensuring that the newly independent Indonesian nation would be modern, democratic, prosperous, and with a concept of social justice based on the state philosophy of Pancasila. In implementing the basic policy, a series of education laws (1950, 1954, 1989 and 2003) have been promulgated that were to produce an educated citizenry who would be ‘intelligent, healthy, moral, democratic, and responsible’. This policy, and the goals and principles of education formulated in the constitution and in subsequent education laws, is in line with a paradigm followed by many nations that have made education an effective means of supporting their growth and development. Education is seen by some economists and political scientists to have a strategic role in improving the quality of life for Indonesian citizens. However, there has been no serious political determination on the part of the elites who control government and parliament to support the implementation of an education system that accords with the hopes and ambition of the Founding Fathers. The funding necessary for education has not been set aside in national budgets despite the constitutional and legislative requirements and expectations that this be done. The funding for education in Indonesia, compared with other developing nations, is low. The goals and principals adopted in the constitution and education laws have not been seriously and consistently implemented.